Perencanaan dan Pengendalian Bahan Baku Sarung Batik (Studi Kasus CV. Mitra Setia Usaha) - Malinda, Debby; Talitha, Tita; Jazuli, Jazuli (Applied Industrial Engineering Journal, 2017)
Planning and controlling the needs of both raw materials and finished products is a significant thing for companies to optimize their production. This also applies to CV. Mitra Setia Usaha thatÂ  engaged in the textile industry with raw materials batik cloth. During this time, CV. Mitra Setia Usaha has not applied standard methods in the planning and control of raw material needs. Determination of the amount of raw materials so far only based on the number of consumer orders. In the last 2 (two years) (October 2014 to September 2016), the company received a request of 5.050,000 meters, but the existing supply of cotton fabric was only 4,920,500 meters. One of the methods that can be applied in the CV. Loyal Business Partners is the Material Requirement Planning (MRP). By applying this MRP-Lot for for lot (LFL) method, CV. Mitra Setia Usaha able to reduce the cost incurred in the procurement of raw materials for one year which initially amounted to 104.328.000 rupiah to 93.817.673 rupiah and can even be reduced again to 83.306.995 rupiah using the method of Order Quantity Period (POQ)